Tristes recuerdos Manila. - National Historical Institute (Philippines). (Manila, Philippines National Historical Commissions of the Philippines, 2011)
Compilation of photographs by Spaniards on the Philippine revolution of 1896.
English and Spanish.
Keywords: Philippines -- History -- Revolution, 1896-1898 -- Pictorial works